Nutrition Misinformation Encountered by Nutritionists in Kulon Progo Regency, Indonesia: A Qualitative Content Analysis - Annisa Usfatun Khasanah; Puji Kurnellawati (Journal of Food, Nutrition, and Health Advances, 2026)
Misinformation about nutrition is a serious public health issue because it can influence eating behaviors and reduce the effectiveness of nutrition programs. This study aims to identify myths and misinformation about nutrition circulating in Kulon Progo Regency and to explore the challenges faced by nutritionists in addressing them. A quantitative descriptive study using content analysis was conducted among 25 nutritionists working at community health centers across all 12 subdistricts in Kulon Progo Regency. Data were collected via an open-ended online questionnaire and analyzed through coding, categorization, theme development, and interpretation. A total of 35 myths and pieces of misinformation were analyzed. The most frequently encountered topics were pregnancy, the introduction of complementary foods, and noncommunicable diseases. Nutritionists also reported challenges in addressing misinformation, such as cultural beliefs, family influence, social media, and limited counseling time. The study’s findings indicate that misinformation is not solely caused by limited nutritional knowledge but is also influenced by sociocultural factors. Therefore, nutrition education should incorporate cultural sensitivity, local contexts, family involvement, and community health workers to enhance the effectiveness of nutrition programs.